The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.31219/osf.io/hgdvp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delayed processing of global shape information in developmental prosopagnosia

Abstract: There is accumulating evidence suggesting that a central deficit in developmental prosopagnosia (DP), a disorder characterized by profound and lifelong difficulties with face recognition, concerns impaired holistic processing. Some of this evidence comes from studies using Navon's paradigm where individuals with DP show a greater local or reduced global bias compared with controls. However, it has not been established what gives rise to this altered processing bias. Is it a reduced global precedence effect, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…The age-related impairment found in this study bears similarity to that proposed in autism (Behrmann et al, 2006;Wallace et al, 2008) and some cases of developmental prosopagnosia (Avidan et al, 2011;Gerlach et al, 2017) to explain face-processing difficulties (although see Joseph & Tanaka, 2003;Thomas et al, 2009). Regardless of the nature of the relative deficits in the different populations, difficulties processing faces are accompanied by problems in relation to communication and social isolation in autism and developmental prosopagnosia, and studies have indicated analogous problems in older populations (Szanto et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…The age-related impairment found in this study bears similarity to that proposed in autism (Behrmann et al, 2006;Wallace et al, 2008) and some cases of developmental prosopagnosia (Avidan et al, 2011;Gerlach et al, 2017) to explain face-processing difficulties (although see Joseph & Tanaka, 2003;Thomas et al, 2009). Regardless of the nature of the relative deficits in the different populations, difficulties processing faces are accompanied by problems in relation to communication and social isolation in autism and developmental prosopagnosia, and studies have indicated analogous problems in older populations (Szanto et al, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…This hypothesis requires further assessment, but is consistent with recent accounts of stronger holistic processing in good recognisers compared to poor ones (DeGutis, Wilmer, Mercado, & Cohan, 2013;Richler, Cheung, & Gauthier, 2011;Wang, Li, Fang, Tian, & Liu, 2012), delayed access to global relative to local shape information in developmental prosopagnosia (Gerlach, Klargaard, Petersen, & Starrfelt, 2017), reports of impaired holistic processing in acquired prosopagnosia (Busigny, Joubert, Felician, Ceccaldi, & Rossion, 2010;Ramon, Busigny, Gosselin, & Rossion, 2016), and the finding that, at the group level, successful familiarisation with novel faces is associated with less focus on local features (Ramon & Van Belle, 2016). …”
Section: Discussionsupporting
confidence: 83%
“…In particular, evidence of selective impairment for SE faces would indicate that the mechanisms recruited by OE and SE faces dissociate (also see Jaquet, Rhodes, & Hayward, 2008;Michel, Rossion, Han, Chung, & Caldara, 2006;Tanaka, Kiefer, & Bukach, 2004;Wiese, Kaufmann, & Schweinberger, 2014). Revealing the breadth of the perceptual impairments in DP also provides important insights into the neurocognitive origins of the condition Biotti, Gray, & Cook, 2017;Geskin & Behrmann, 2017); for example, evidence of typical recognition of OE faces would argue against domain-general accounts of the condition (Avidan, Tanzer, & Behrmann, 2011;Gerlach, Klargaard, Petersen, & Starrfelt, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some accounts of DP clearly predict impaired perception of OE faces, relative to experiencematched controls. For example, it has been argued that delayed or impoverished processing of global shape information produces a wide range of visual deficits in DP, including face and non-face object recognition difficulties (Avidan et al, 2011;Gerlach et al, 2017;Tanzer, Freud, Ganel, & Avidan, 2013). Provided both groups have equal opportunities to develop perceptual expertise, this account predicts that DPs should exhibit poorer recognition of OE faces relative to controls.…”
Section: Introductionmentioning
confidence: 99%